2001
DOI: 10.1051/0004-6361:20000047
|View full text |Cite
|
Sign up to set email alerts
|

First light measurements with the XMM-Newton reflection grating spectrometers: Evidence for an inverse first ionisation potential effect and anomalous Ne abundance in the Coronae of HR 1099

Abstract: Abstract. The RS CVn binary system HR 1099 was extensively observed by the XMM-Newton observatory in February 2000 as its first-light target. A total of 570 ks of exposure time was accumulated with the Reflection Grating Spectrometers (RGS). The integrated X-ray spectrum between 5-35Å is of unprecedented quality and shows numerous features attributed to transitions of the elements C, N, O, Ne, Mg, Si, S, Fe, and Ni. We perform an in-depth study of the elemental composition of the average corona of this system,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(171 citation statements)
references
References 24 publications
14
157
0
Order By: Relevance
“…Such a Ne abundance enhancement is reminiscent of a similar anomaly observed in a subset of solar flares (Murphy et al 1991;Schmelz 1993). Large Ne abundance enhancements are a common feature of active stellar coronae (Güdel et al 2001;Huenmoerder et al 2001) and an inverse FIP effect is observed in very active coronae Drake et al 2001) where the abundances (relative to oxygen) increase with increasing first ionization potential (FIP). The emitting volume of the different plasma components could be constrained if their electron densities were known.…”
Section: Obsmentioning
confidence: 82%
“…Such a Ne abundance enhancement is reminiscent of a similar anomaly observed in a subset of solar flares (Murphy et al 1991;Schmelz 1993). Large Ne abundance enhancements are a common feature of active stellar coronae (Güdel et al 2001;Huenmoerder et al 2001) and an inverse FIP effect is observed in very active coronae Drake et al 2001) where the abundances (relative to oxygen) increase with increasing first ionization potential (FIP). The emitting volume of the different plasma components could be constrained if their electron densities were known.…”
Section: Obsmentioning
confidence: 82%
“…The abundance trends found in other systems show that low-FIP species are subsolar, while high-FIP elements (neon) have enhanced abundance Drake et al 2001;Audard, Gü del, & Mewe 2001;Brinkman et al 2001;Güdel et al 2001aGüdel et al , 2001b. However, we find that the lowest FIP elements have intermediate abundances, as does the high-FIP element Ar, relative to the other elements.…”
Section: Discussionmentioning
confidence: 97%
“…However, a reverse pattern called the "inverse FIP effect" (IFIP) is observed in active stars (e.g. Brinkman et al 2001;Audard et al 2003). As can be seen in Fig.…”
Section: Fip Effectmentioning
confidence: 95%